Effectiveness and economic evaluation of a nurse delivered home exercise programme to prevent falls. 1: Randomised controlled trial. Issue 7288 (24th March 2001) - Robertson, M Clare; Devlin, Nancy; Gardner, Melinda M; Campbell, A John
Abstract: Objectives: To assess the effectiveness of a trained district nurse individually prescribing a home based exercise programme to reduce falls and injuries in elderly people and to estimate the cost effectiveness of the programme. Design: Randomised controlled trial with one year's follow up. Setting: Community health service at a New Zealand hospital. Participants: 240 women and men aged 75 years and older. Intervention: 121 participants received the exercise programme (exercise group) and 119 received usual care (control group); 90% (211 of 233) completed the trial. Main outcome measures: Number of falls, number of injuries resulting from falls, costs of implementing the programme, and hospital costs as a result of falls. Results: Falls were reduced by 46% (incidence rate ratio 0.54, 95% confidence interval 0.32 to 0.90). Five hospital admissions were due to injuries caused by falls in the control group and none in the exercise group. The programme cost NZ1803 (£523) (at 1998 prices) per fall prevented for delivering the programme and NZ155 per fall prevented when hospital costs averted were considered. Conclusion: A home exercise programme, previously shown to be successful when delivered by a physiotherapist, was also effective in reducing falls when delivered by a trained nurse from within a home health service. Serious injuries and hospital admissions due to falls were also reduced. The programme was cost effective in participants aged 80 years and older compared with younger participants.